Economics of legume-wheat (Triticum aestivum) cropping systems under different levels of irrigation - Singh, Ved; Ramdev, Ramdev; Sharma, S K; Siag, R K; Verma, B L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted from 1988-89 to 1992-93 to evaluate the productionpotential and economic returns in wheat (Triticum aestivum L. emend. Fiori & Paol.}-basedcropping system under various levels of irrigation. Greengram (Phaseolus radiatus L.)-wheat,pigeonpea [Cajanus cajan (L.) Millsp.), wheat and clusterbean [Cyamopsis tetragonaloba (L.)Taubert)-wheat cropping systems gave maximum economic yields and net returns withrespectively 8, 11 and 8 irrigations during rainy and winter Seasons. Among the rainy-seasonlegumes, pigeonpea gave the maximum seedyield (1.81 tonnes/ha) with 5 irrigations applied atirrigation water: cumulative pan evaporation (IW : CPE) ratio of 5, followed by clusterbeanand greengram. Pigeonpea-wheat cropping system receiving 11 irrigations showed the highesteconomic yield (4.61 tonnes/ha/year) and wheat-equivalent yield (5.84 tonnes/ha/year), totalnet return (Rs 16831/ha/year) and consumptive use of water (863 mm). Significantly highestmean net return of Rs 13 158/ha/year Was obtained from pigeonpea-wheat cropping system,followed by clusterbean - wheat and greengram-wheat. The highest mean values for cost ofcultivation (Rs 8 725ha/year), net return (Rs 46.49/ha/day), consumptive use (807 mm water)and land-use efficiency (77.53%) were recorded with pigeonpea-wheat, followed byclusterbean-wheat and greengram-wheat. Maximum water-use efficiency of 5.67 kg/ha-mm wasrecorded in clusterbean-wheat, whereas highest harvest index (26.4%) and productionefficiency ( 15.36 kg/ha/day) were obtained in greengram-wheat cropping system.